Effects of DNA Methylation on TFs in Human Embryonic Stem Cells - Luo, Ximei; Zhang, Tianjiao; Zhai, Yixiao; Wang, Fang; Zhang, Shumei; Wang, Guohua (Frontiers in Genetics, 2021)
DNA methylation is an important epigenetic mechanism for gene regulation. The conventional view of DNA methylation is that DNA methylation could disrupt the protein-DNA interactions and repress gene expression. Several recent studies reported that DNA methylation could alter the TFs’ binding sequence specificity in vitro. Here, we took advantage of the large sets of ChIP-seq data for TFs and whole-genome bisulfite sequencing data in many cell types to perform a systematic analysis of the protein-DNA methylation in vivo. We observed that many TFs could bind methylated DNA regions, especially in H1-hESC cell. By locating binding sites, we confirmed that some TFs could bind to methylated CpGs directly. The different proportion of CpGs at TF binding specificity motifs in different methylation status shows that some TFs are sensitive to methylation and some could bind to the methylated DNA with different motifs, such as CEBPB and CTCF. At the same time, TFs binding could alter the local DNA methylation interactively. The TF hypermethylation binding sites extensively overlap with enhancers. And we also found that some DNase I hypersensitive sites are hypermethylated in H1-hESC cell specifically. At last, comparing with TFs’ binding regions in multiple cell types, we observed CTCF binding high methylated regions in H1-hESC are not conservative. These pieces of evidence indicate that TFs bind to hypermethylation DNA in H1-hESC cell may associate with enhancers to regulate special biological functions.